2020
DOI: 10.3906/tar-1903-36
|View full text |Cite
|
Sign up to set email alerts
|

Properties of fiberboards produced from kermes oak (Quercuscoccifera L.) and brutian pine (Pinusbrutia Ten.) woods

Abstract: In this study the utilization of kermes oak (Quercus coccifera L.) wood, which could be used as an industrial raw material for the production of fiberboard, was investigated. In the experimental design, boards were produced from mixtures of kermes oak and brutian pine (Pinus brutia Ten.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 31 publications
4
0
0
Order By: Relevance
“…The main chemical components of Brutian pine wood and pulp samples are listed in Table 1. The holocellulose contents of wood samples were in agreement with the values of 70.8%, 72.57%, 72.07%, 72.64%, and 72.09% reported for Brutian pine wood by Kırcı (1991), Kılıç et al (2010), Güler and Yaşar (2018), Beram and Yasar (2020), and Güler and Yaşar (2020). Similarly, the α-cellulose contents of wood samples were consistent with the values of 48.56%, 46.5%, 48.16%, 48.23%, and 48.24% observed by Tutuş et al (2012), Taş (2017), Güler and Yaşar (2018), Beram and Yasar (2020), and Güler and Yaşar (2020).…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…The main chemical components of Brutian pine wood and pulp samples are listed in Table 1. The holocellulose contents of wood samples were in agreement with the values of 70.8%, 72.57%, 72.07%, 72.64%, and 72.09% reported for Brutian pine wood by Kırcı (1991), Kılıç et al (2010), Güler and Yaşar (2018), Beram and Yasar (2020), and Güler and Yaşar (2020). Similarly, the α-cellulose contents of wood samples were consistent with the values of 48.56%, 46.5%, 48.16%, 48.23%, and 48.24% observed by Tutuş et al (2012), Taş (2017), Güler and Yaşar (2018), Beram and Yasar (2020), and Güler and Yaşar (2020).…”
Section: Resultssupporting
confidence: 90%
“…The holocellulose contents of wood samples were in agreement with the values of 70.8%, 72.57%, 72.07%, 72.64%, and 72.09% reported for Brutian pine wood by Kırcı (1991), Kılıç et al (2010), Güler and Yaşar (2018), Beram and Yasar (2020), and Güler and Yaşar (2020). Similarly, the α-cellulose contents of wood samples were consistent with the values of 48.56%, 46.5%, 48.16%, 48.23%, and 48.24% observed by Tutuş et al (2012), Taş (2017), Güler and Yaşar (2018), Beram and Yasar (2020), and Güler and Yaşar (2020). Lignin contents of wood samples in this study were higher than the previously reported klason lignin contents of 27.4%, 27.34%, 27.60%, 27.16%, 27.98%, and 27.33% demonstrated by Kırcı (1991), Kılıç et al (2010), Tutuş et al (2012), Güler and Yaşar (2018), Beram and Yasar (2020), and Güler and Yaşar (2020).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations